Characterization, experimental and simulation of heat transfer performance for Al2O3-TiO2-SiO2 ternary nanofluid with inserts - Anwar Ilmar, Ramadhan (2023)
Heat transfer research has received significant attention for a long time and has been found in various applications, including cooling electronic devices, manufacturing systems, and solar energy systems. In recent years, nanofluids and inserts have been used to boost further the heat transfer performance for passive techniques with the compound method. However, there has been limited research on ternary nanofluids with a wire coil and twisted tape. The ternary nanofluids are considered due to their advantages in overcoming the stability drawback of mono and binary nanofluids. Meanwhile, the wire coil and twisted tape are used in the present study because they provide maximum heat transfer enhancement with the least friction penalty among the inserts. Therefore, this study aims to characterize and evaluate the thermo-physical properties, heat transfer performance, and thermal performance factor (TPF) of Al2O3-TiO2-SiO2 ternary nanofluids with a wire coil and twisted tape under experimental and simulation conditions. The ternary nanofluids were initially formulated using the optimum composition ratio of 20:16:64 by volume percent. The nanofluids were then prepared in various volume concentrations ranging from 0.5 to 3.0%. The stability of the ternary nanofluid was investigated using qualitative and quantitative methods. Thermal conductivity and dynamic viscosity of ternary nanofluids were measured with KD2 Pro Thermal Properties Analyzer and Brookfield LVDV III Rheometer. Experimental forced convection heat transfer was carried out using a fabricated setup. The experimental work was undertaken for a wide range of Reynolds numbers from 2,300 to 12,000 at bulk temperature of 70 °C. Experiments were performed at constant heat flux boundary conditions for flow in plain tubes with wire coil inserts (0.83 ≤ P/D ≤ 2.50) and with twisted tape (2.0 ≤ H/D ≤ 5.0). Simulation models of ternary nanofluids are developed for a plain tube, wire coil and twisted tape and validated using grid independence analysis. Simulations were performed using Computational Fluid Dynamics (CFD) with standard k-ε model to determine the flow pattern, temperature distribution, and heat transfer and friction factor of ternary nanofluids under similar experimental conditions but at higher Reynolds number of more than 12,000. The ternary nanofluids were confirmed under excellent stability conditions with a high zeta potential of up to 63.72 mV. The highest thermal conductivity enhancement of 24.8% was obtained for ternary nanofluids at 3.0% volume concentration. The 3.0% volume concentration also shows the highest viscosity at all temperatures. Based on experimental, the maximum heat transfer improvement for ternary nanofluids in a plain tube, with wire coil (P/D-0.83) and twisted tape (H/D-2.0), was attained by 3.0% volume concentration of up to 21.46%, 199.23% and 225.35%, respectively. The ternary nanofluids with twisted tape improve the TPF by up to 3.22 at 3.0% volume concentration, significantly higher than plain tube and wire coil conditions. The present simulation for ternary nanofluids with plain tube, wire coil and twisted tape can effectively predict the Nusselt number and friction factor with a good agreement between the simulation with ANSYS and experimental data. In conclusion, the Al2O3-TiO2-SiO2 ternary nanofluids enhanced the properties and improved the heat transfer performance with a wire coil and twisted tape. The ternary nanofluids at 3.0% volume concentration with twisted tape at H/D = 2.0 were recommended for heat transfer application such as heat exchanger and automotive cooling system to provide with the highest TPF.